Pulse oximetry and clinical changes during electrosurgery in dogs anaesthetized with Xylazine-Thiopentone and Xylazine-Ketamine combinations - Munif, Mohammad Raguib; Alam, Md Mahmudul; Alam, Md Rafiqul (Research in Agriculture Livestock and Fisheries, 2020)
This study was performed to explore the pulse oximetric evaluation of cardio-respiratory systems along with the determination of body temperature in dogs anaesthetized with xylazine-thiopentone (X-T) and xylazine-ketamine (X-K) combinations during electrosurgery. Six apparently healthy dogs weighed 20 to 25 kg undergoing electrosurgery (bipolar), were divided into two groups: group A (X-T) and group B (X-K). In group A (n=3), dogs were anaesthetized with xylazine @ 1.1 mg/kg body weight (BW) as intramuscular (IM) and thiopentone @ 20 mg/kg BW as intravenous (IV) injections, and in group B (n=3), dogs were anaesthetized with xylazine @ 1.1mg/kg BW IM and ketamine @ 5.5 mg/kg BW IM after premedication with atropine sulphate @ 0.05 mg/kg BW IM. Bipolar electrosurgery for gastrotomy or castration was performed in the dogs. Pulse oximetric monitoring and the evaluation of clinical changes: heart rate, respiratory rate and peripheral blood oxygen saturation (SpO2) were done along with the determination of body temperature before the induction of anaesthesia (control) and thereafter on 10, 20, 30, 40 and 50 minutes postinduction in both groups during electrosurgery. Temperature, heart rate and respiratory rate were altered significantly (P<0.05) during the experimental period in both groups as compared to the control values. SpO2 was decreased significantly (P<0.05) throughout the experiment and returned to the level of initial control value after complete recovery in both groups. These findings revealed that during electrosurgery in dogs the anaesthetic combinations of X-T and X-K exert certain clinical changes in the vital signs (body temperature, heart rate, respiratory rate) and SpO2 which should be carefully considered to take necessary steps for perioperative patient’s safety and recovery. Res. Agric., Livest. Fish.7(1): 97-105, April 2020